2020
DOI: 10.1155/2020/7817542
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Injections for Macular Edema Secondary to Retinal Vein Occlusion: Long-Term Functional and Anatomic Outcomes

Abstract: Purpose. To report the long-term visual and anatomic outcomes of intravitreal injections for macular edema (ME) secondary to retinal vein occlusion (RVO) in a real-life clinical setting. Design. Retrospective interventional case series. Methods. A total of 223 consecutive eyes with ME secondary to RVO, treated with the first three intravitreal Ranibizumab or dexamethasone injections between August 2008 and September 2018, were enrolled in the study. Subsequent retreatment was guided by best-corrected visual ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…The visual gain of at least 3 lines in 62% of eyes at 1 year in our series is also similar to other studies on RVO [11,12] but superior to those reported by Spooner et al using bevacizumab, ranibizumab, or aflibercept in a Caucasian population [21]. Long-term visual outcomes following intravitreal anti-VEGF therapy have been reported by Spooner et al and Maggio et al [21,22]. The retrospective study of Spooner et al [21] included 68 eyes with RVO; observed visual gains at 1 year were maintained at [22] also found significant visual gain at 4 years following flexible dosing regimen of ranibizumab and dexamethasone in eyes with ME associated with RVO.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The visual gain of at least 3 lines in 62% of eyes at 1 year in our series is also similar to other studies on RVO [11,12] but superior to those reported by Spooner et al using bevacizumab, ranibizumab, or aflibercept in a Caucasian population [21]. Long-term visual outcomes following intravitreal anti-VEGF therapy have been reported by Spooner et al and Maggio et al [21,22]. The retrospective study of Spooner et al [21] included 68 eyes with RVO; observed visual gains at 1 year were maintained at [22] also found significant visual gain at 4 years following flexible dosing regimen of ranibizumab and dexamethasone in eyes with ME associated with RVO.…”
Section: Discussionsupporting
confidence: 91%
“…Significant reduction in CSFT in eyes with RVO following administration of IVZ on prn bases has been reported similar to this series [15][16][17]. These observations are further supported by other studies on outcome of ME associated with RVO-treated other anti-VEGFS [9][10][11][12][13][21][22][23]. In our study, baseline CSFT and mean reduction in reduction in CFST were not significantly different between BRVO and CRVO, although VA was significantly better in the BRVO compared to CRVO group in all visits.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations